8x+7-11x+10=10x-13x+11

Simple and best practice solution for 8x+7-11x+10=10x-13x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+7-11x+10=10x-13x+11 equation:


Simplifying
8x + 7 + -11x + 10 = 10x + -13x + 11

Reorder the terms:
7 + 10 + 8x + -11x = 10x + -13x + 11

Combine like terms: 7 + 10 = 17
17 + 8x + -11x = 10x + -13x + 11

Combine like terms: 8x + -11x = -3x
17 + -3x = 10x + -13x + 11

Reorder the terms:
17 + -3x = 11 + 10x + -13x

Combine like terms: 10x + -13x = -3x
17 + -3x = 11 + -3x

Add '3x' to each side of the equation.
17 + -3x + 3x = 11 + -3x + 3x

Combine like terms: -3x + 3x = 0
17 + 0 = 11 + -3x + 3x
17 = 11 + -3x + 3x

Combine like terms: -3x + 3x = 0
17 = 11 + 0
17 = 11

Solving
17 = 11

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -5/13x=-2 | | 4.3v+6=2.3v-2 | | 2(-3)+2y=20 | | -2(4x+3)-8=6+2x | | 36=18-8t | | (10x+4)-(9x+7)=-6 | | 2*x=1.5*13.3 | | 3(n+4)=-3(4+n) | | 5[7-5(6-q)]-7=7[(7q-6)+4]-50 | | (x^4-2.3x^3+6)(x^4-2.3x^3+6)=0 | | 4-6lnx=y | | -2x=2y-4 | | 4x+11=4x-21 | | -9(x-1)=-8x-6 | | 3(2x-2)=5(x+4) | | 8+2x=-x+35 | | 8y-2=9y-2y | | 3r-5r+r+8= | | 50/1x=3 | | 5x+10=64-x | | 3x^6+15x^4-12x^2=0 | | s-9=11 | | -5+4x+3x=-33 | | log(4)(x+2)=3 | | 4(-6+x)=16 | | 3(x+8)+5x=8x-24 | | 6(3x+8)=228 | | -6x+2y=34 | | 3(5x+9)=-37+19 | | 6(-9-x)=-24 | | 2(2x)=32 | | -8(8x-6)=-6x-228 |

Equations solver categories